PEMANFAATAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN FIKIH DI MTS SALAFIYAH SYAFI’IYAH SEBLAK JOMBANG - Pratama, Dian Agung Dewi; Anshori, Sholihul; Salim, Muhammad Nur (EL-Islam, 2022)
Abstract: Media is one of the important learning components. The researcher aimss to describe the implementation of Fiqh learning along with the use of audio-visual media in improving the quality of Fiqh learning at MTs Salafiyah Syafi'iyah Seblak Jombang. Furthermore, this research is to reveal the supporting and inhibiting factors of the learning process. This type of research uses case study research. The research was conducted using a descriptive approach and qualitative research methods. Data collection was carried out through interviews, observation techniques, and documentation. In this study, the informants consisted of fiqh teachers, who taught class IX and students in class IX. The data collected from observations and interviews were then analyzed using the triangulation analysis technique of data sources. Based on the results of the study, it was found that: Fiqh teachers at MTs Salafiyah Syafi'iyah Seblak Jombang used audio-visual media in learning through the following steps: observing, studying, and re-checking that the tools to be used were working properly, then students were asked to watch the video. then students are directed that when watching the video record important materials, and after that explain the subject matter further then question and answer and practice Then apply or practice according to the content of the material, and the teacher if there is something wrong in the discussion earlier. Supporting factors in the use of audio-visual media in improving the quality of fiqh learning at MTs Salafiyah Syafi'iyah Seblak Jombang are the availability of complete facilities and a conducive environment. The inhibiting factors are from students, such as there are still hexagons, sleeping and noisy in class, and from the teacher's perspective, namely the low level of professional competence.